Some reasons that influence dropout in a Physics Teachers Training program - Kussuda, S. R. [UNESP]; Nardi, R. [UNESP] (IOP Publishing, 2019)
There currently exist several countries experiencing problems related to the lack of teachers, as indicates the Organization for Economic Cooperation and Development. Part of this problem is related to the quantity of students that dropout teacher training programmes, reducing the quantity of teaching workforce. We conducted a research to understand the main reasons to former students to dropout a physics teachers training programmes. To obtain the data we applied an online questionnaire with 274 former students, 37 of them answered the questionnaire. Although this number represents 13.5% of the total, the main answers are recurrent, indicating that those could be similar to other former students. Through the analysis of the answers was possible to note that, although this physics' teaching programme may be considered difficult among former students, such difficulties seem to be related to several factors, beside the complexity of the Physics as need to work during the morning or the demotivation that occurs within this programme. We argue that the dropouts seem to be more related to problems such as the pedagogical performance of the professors of Higher Education, than difficulties related the complexity of Physics.